Current Trends in Hypertension: Takeaways from the 2021 KDIGO Guidelines for the Management of Blood Pressure in Chronic Kidney Disease - Tinawi, Mohammad (Cardiology and Cardiovascular Medicine, 2022)
The new 2021 Kidney Disease Improving Global Outcomes (KDIGO) guidelines on the management of blood pressure in chronic kidney disease (CKD) patients were published in March 2021 in Kidney International. The full issue exceeds 80 pages. The author of this article aims to provide a succinate summary of the main points of the guidelines with special emphasis on the changes introduced since the previous 2012 guidelines. These KDIGO guidelines are evidence-based, and they are graded accordingly. As with any recent hypertension guidelines, they incorporate and emphasize the results of The Systolic Blood Pressure Intervention Trial (SPRINT) pub-lished in 2015.